A study on some phrasal verbs in business texts in English from cognitive semantic perspective = Nghiên cứu nghĩa của một số cụm động từ tiếng Anh trong ngữ cảnh tiếng Anh kinh tế dưới góc độ ngữ nghĩa tri nhận. M.A. Thesis Linguistics: 60 22 15 - Ngô, Thị Việt Anh (University of Languages and International Studies, 2017)
Chapter I: Theoretical background. Chapter II: The study. Chapter III: Conclusion.